HUBUNGAN TINGKAT KECEMASAN IBU PRIMIPARA DENGAN KELANCARAN PROSES PERSALINAN DI RB ANANDA JABON MOJOKERTO - Yulianti, Indra (JURNAL KEPERAWATAN BINA SEHAT, 2015)
Partus a result expenditure process conception that can alive in uterus pass vagina to world outside. worried emotion response without object specific objectively undergone and communicated according to interpersonal. Partus process not has only somatic but psychosomatic, many elements psikis that come along to influence partus process. phenomenon at field either in house birth to also reaction hospital psikologis from mother birth to multifarious kind and vary from every individual. This matter depending from mother immediacy faces partus and mechanism coping mother in restrain the emotion. Watchfulness design that used analytic with method cross sectional. sample in this watchfulness numbers 20 respondents with total technique sampling. Data taking manner by using questioner that given in mother primipara then done process partus observation by researcher. Data processing uses sign correlation statistics test (test t). From watchfulness result is got half respondent (50%) experiences light worried and more than half mother primipara (70%) pass partus process at ease. Sign correlation statistics test result is got value significant 0,005. should mother primipara more increase erudition and look for information about partus process so that mother more self confidence and can to do coping moment face worried in partus.Keyword:Partus, Mother Anxiety Primipara